Preliminary Damage Assessment Due To 2015 Ranau Earthquake - T. A., Majid; A., Adnan; M. I., Adiyanto; M. Z., Ramli; T. C., Ghuan (Penerbit UMP, 2017)
Since December 2004, there was a lot of tremors felt in Malaysia. Most of the tremors occurred due to Sumatra Andaman and Philippine earthquakes. Several local earthquakes in Bukit Tinggi, Pahang also reported in 2007. These events did not caused any damages on buildings. However, on June 5th 2015, a moderate earthquake with magnitude Mw5.9 as reported by Malaysian Meteorological Department was occurred in Sabah, Malaysia around 7:15 am local time. The epicentre was located at 16 km northwest from Ranau and the depth is 54 km beneath the earth. The tremors was felt in Ranau, Kundasang, Tambunan, Pedalaman, Tuaran, Kota Kinabalu, and Kota Belud. The main-shock also followed by several tremors namely as after-shock. For the sake of safety, it is very important to examine the condition of existing buildings shortly after earthquake. Therefore, less than two days after the first event, a reconnaissance mission took action to investigate the damages on buildings. This paper presents the structural damages occurred on reinforced concrete buildings due to 2015 Ranau earthquake. Based on in-situ field observation, it is clear that the columns experienced significant damage compared to beams. This failure mechanism is known as Weak Column–Strong Beam. The damages due to soft-storey mechanism and short column effect also occurred on the reinforced concrete buildings due to the earthquake event.